Perception on Social Media Advertising among Malaysian Youth - Anand, Archana (2013)
A rapid growth and an increasing popularity of social media such as Facebook, Youtube, Twitter etc. have drawn more and more attention from marketers and researchers. Companies now are throwing big money at advertising on social media, hoping to attract consumer’s attention. But questions remain unanswered regarding the social media users’ perception towards social media advertising and also the factors affecting their attitudes towards it. Unfortunately, there is a lack of quantitative studies on social media users’ perception of or attitudes towards advertising on social media. So this research aims at investigating social media users’ perception towards social media advertising. This study is confined to the Malaysian youth who are between the age of 18 to 25 years due to the fact that they engage in social media more when compared to the other age groups. Both primary and secondary data were used as the instrument in this survey. All 250 questionnaires will be distributed equally to male and female respondents. Out of the 250 questionnaire, 180 were effective. Reliability analysis was done to check the relationship between the independent and dependent variables. The findings of this study indicates that there is a significant association between In formativeness, Credibility, Entertainment, and User perception toward social media advertising. It also indicates that there is no association between privacy and security concern and user perception towards social media advertising.